Basic immunology : - Abbas, Abul K. (Saunders Elsevier, 2009)
Introduction to the immune system, Innate immunity, Antigen capture and presentation to lymphocytes, Antigen recognition in the adaptive immune system, Cell-mediated immune responses, effector mechanisms of cell-mediated immunity, Humoral immune responses, Effector mechanisms of humoral immunity, immunological tolerance and autoimmunity, Immune responses against tumors and transplants, Hypersensitivity, ...